Peran ukuran perusahaan dalam hubungan antara dewan direksi, komite audit dan likuiditas dengan profitabilitas - Fatimah, Dewi; Rahman, Taufikur (Nur Science Institute, 2021)
This study aims to determine the effect of the Board of Directors, Audit Committee, and Liquidity on Profitability with Company Size as Moderating Variable in Islamic Banking in Indonesia for the 2016-2020 period. This type of research is quantitative research with secondary data in panels. The number of samples in this study is 11 Islamic Commercial Bank using the purposive sampling method with criteria determined by researchers. The analytical method used is the Moderated Regression Analysis (MRA) test. The results show that the board of directors and audit committee harm profitability; the current ratio positively affects profitability. The Moderated Regression Analysis (MRA) test shows that company size can moderate the effect of the audit committee on profitability. However, company size cannot moderate the influence of the board of directors and current ratio on profitability.